Ethical product decision involvement and its moderating effects on the relationship between consumers' motivational factors and ethical fashion purchase intention - Celestial, Czarlyna Louise M. (Animo Repository, 2022)
A lack of resources pertaining to the study concerning ethical fashion and consumers’ purchase intention was identified by the researchers despite the recent upsurge of ethical fashion awareness. Hence, this study was conducted to determine the extent to which ethical product decision involvement influences the relationship between Philippine consumers’ motivational factors (attitude, perceived behavioral control, subjective norm, moral obligation, and self-identity) and their purchase intention towards ethical fashion products. Ethical Product Decision Involvement was applied as a moderating variable to the framework of The Extended Theory of Planned Behavior (TBP) with consumers’ ethical fashion purchase intention as the dependent variable. The respondents of this study are 18-34 years old who reside in the National Capital Region (NCR) and have made a fashion item purchase within the previous year. A sample size of 400 was calculated by the researchers and a combination of the convenience and snowball sampling methods were used for this study. A pilot test among 30 respondents was conducted to test the reliability and validity of the survey questionnaire. The results of the official data gathering proper were collected, They were analyzed using simple linear regression, multiple linear regression, and moderated multiple regression. These statistical methods helped determine the relationship between consumers’ motivational factors and ethical fashion purchase intention, and the extent to which ethical product decision involvement influences it. After analyzing the results from the data gathered, results from the moderated multiple regression showed that ethical product decision involvement (EPDI) only had a significant interaction effect with subjective norm (SUB) among the five independent variables, however, it was found to have a negative effect on purchase intention (PUR). Hence, the relationship of subjective norm and purchase intention is better explained when accounting for ethical product decision involvement of consumers. Consequently, it is recommended for consumers to acquire moral certainty in order to have intrinsic moral values which will guide them in having ethical and moral judgments, not solely relying on subjective norms. With the findings of the study, it was recommended that in order to amplify ethical product decision involvement (EPDI) towards having a significant effect on the other independent variables with regard to purchase intention, ethical businesses must establish and recognize the importance of trust among their customers while leaning towards a better ethical marketing strategy that may encourage higher ethical product decision involvement among customers.